MANAJEMEN KURIKULUM PENDIDIKAN DALAM PENERAPAN KURIKULUM 2013 DI SMP SWASTA IT DHINUKUM ZHOLTAN - Mulia Ramadhan Sitepu, Yuda; Neliwati, Neliwati; Nazah, Nadia; Manurung, Istiqomah; Solehatun, Sri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Educational curriculum management is a systematic process to achieve educational goals. In implementing the 2013 curriculum, education curriculum management needs to be done well so that educational goals can be achieved effectively and efficiently. This research aims to find out how the education curriculum is managed in implementing the 2013 curriculum at Dhinikum Zholtan IT Private Middle School. This research uses qualitative research methods with a descriptive approach. The data collection techniques used were observation, interviews and documentation. The results of the research show that the management of the educational curriculum at Dhinikum Zholtan IT Private Middle School is running well. This can be seen from the systematic planning, implementation and evaluation of the curriculum. Curriculum planning is carried out by involving all stakeholders, namely school principals, teachers and school committees. The implementation of the curriculum is carried out in accordance with the RPP that has been prepared. Curriculum evaluation is carried out periodically to determine the achievement of educational goals.